2018
DOI: 10.1111/epi.14527
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐month prospective randomized controlled trial of remotely delivered group format epilepsy self‐management versus waitlist control for high‐risk people with epilepsy

Abstract: SMART is associated with reduced health complications and improved mood, quality of life, and health functioning in high-risk people with epilepsy. Additional efforts are needed to investigate potential for scale-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 37 publications
1
31
0
2
Order By: Relevance
“…Targeted Training for Illness Management (TTIM) is an evidence-based, manualized, modular group intervention for the self-management of chronic illness, originally developed for people with severe mental illness. The evidence-based TTIM approach has been successfully adapted for a variety of chronic health conditions including epilepsy, stroke, Parkinson's disease, and diabetes [32][33][34][35][36]. TTIM was selected for this study by our stakeholders because it met the criteria for having both physical and mental health topics and had a version specific to diabetes.…”
Section: Curriculummentioning
confidence: 99%
“…Targeted Training for Illness Management (TTIM) is an evidence-based, manualized, modular group intervention for the self-management of chronic illness, originally developed for people with severe mental illness. The evidence-based TTIM approach has been successfully adapted for a variety of chronic health conditions including epilepsy, stroke, Parkinson's disease, and diabetes [32][33][34][35][36]. TTIM was selected for this study by our stakeholders because it met the criteria for having both physical and mental health topics and had a version specific to diabetes.…”
Section: Curriculummentioning
confidence: 99%
“…One in the USA looked at the delivery of self-management intervention for people with epilepsy and a history of negative health events (SMART) using wide ranging assessment tools. It found that participants who had better SMART attendance had a reduction in negative health events counts (NHE), and seizure frequency, from base line to six month when compared to controls, however, seizure severity was not reduced, and no significance was found when specifically looking at ED attendance [22]. A US quality improvement project looked at the use of educational materials focusing on self-management and seizure first aid, such as educational handouts and a DVD, to see whether they reduced ED attendances.…”
Section: Educational Interventionsmentioning
confidence: 99%
“…Six reports looked at educational programmes for people living with epilepsy attending EDs [22][23][24][25][26][27]. One in the USA looked at the delivery of self-management intervention for people with epilepsy and a history of negative health events (SMART) using wide ranging assessment tools.…”
Section: Educational Interventionsmentioning
confidence: 99%
“…Specifically, only one RCT-by Sajatovic et al 60 has considered change in ED use following epilepsy self-management. 61 Conducted in the USA, it compared 'Self-MAnagement for people with epilepsy and ahistoRy of negative health evenTs' (SMART)-an 8-session group intervention-to wait list control.…”
Section: Discussionmentioning
confidence: 99%